FORMATION AND ENSURING SAFETY IN HOTEL AND RESTAURANT BUSINESS ENTERPRISES (Development Service Industry Management, 2025)
The article is devoted to the study of the issue of ensuring security at the enterprises of the hotel and restaurant business under martial law. The main threats that may affect the work of hotels and restaurants are highlighted. The fundamental provisions of the security system of hospitality industry establishments and the types of security systems are considered. It is proven that the correct application of the system increases the level of hotel and restaurant security, their rating and image. The implementation of new trends in the field of security requires careful planning, investment and constant updating. A model for the formation of the competencies of security service specialists in hotel and restaurant business establishments is proposed. It was found that for effective management of a hotel and restaurant business during wartime, it is necessary to develop a comprehensive strategy that takes into account all aspects of security and economic sustainability. The key elements of such a strategy are ensuring the safety of guests and staff, minimizing costs and optimizing business processes, as well as preserving the reputation and attractiveness of the hotel for customers. To achieve goals, it is necessary to use innovative approaches to management, actively implement technological solutions to improve business security and efficiency, as well as constantly monitor the situation and flexibly adapt to changes. It has been proven that it is important for an institution to have qualified and experienced staff who can effectively respond to emergencies and make informed management decisions in times of uncertainty and crisis. The study confirmed that ensuring security in wartime requires appropriate strategies and planning to ensure the protection of guests and staff in unforeseen circumstances. It is important to pay attention to preparing staff to respond to emergencies and training them to act effectively in crisis situations.
Keywords: hotel and restaurant business; strategies; security; martial law; risks; security systems